A deep dive into the dynamics of indigenous crops: nutritional value, production patterns, and market accessibility in Southern Highlands of Tanzania - John, Innocensia; Vicent, Victor (Frontiers in Sustainable Food Systems, 2025)
This study explores the value chain of selected indigenous crops in Tanzania, assessing their potential to address micronutrient deficiencies and contribute to food security. The research examines production patterns, processing techniques, and market dynamics, identifying key challenges and opportunities within the value chain. Crops such as amaranth, sorghum, millet, and baobab are cultivated using traditional methods, integrating local knowledge and organic inputs. The study highlights major constraints, including limited market linkages, inadequate processing infrastructure, and weak policy support, which hinder the commercialization and accessibility of these crops. Key findings reveal that while indigenous crops are widely produced and consumed, their market presence remains low due to inefficiencies in distribution channels and consumer awareness gaps. The study underscores the high nutritional value of these crops, particularly their rich content of iron, zinc, and pro-vitamin A, making them crucial in addressing malnutrition. The research further identifies opportunities for value chain improvements, such as enhanced processing methods, improved storage facilities, and policy interventions to support smallholder farmers. The study concludes that strengthening the indigenous crop value chain through targeted investments in infrastructure, policy support, and market development can transform these crops into competitive commodities. Recommendations include increasing consumer education, integrating digital marketing platforms, and fostering collaborations between stakeholders to enhance production efficiency and market access. By addressing these challenges, indigenous crops can play a pivotal role in sustainable agriculture, improving nutrition, and bolstering the livelihoods of rural farmers in Tanzania.